SOCIAL NETWORK IN FAMILY BUSINESS: THE PHENOMENON OF PONOROGO CHINESE ETHNIC ENTREPRENEUR - Hadi Sumarsono; Khusnatul Zulfa Wafirotin; Slamet Santoso (School of Business, IPB University (SB-IPB), 2021)
The dominance of Chinese ethnic businesses in Ponorogo is thought to be related to their strong business networks. This study aims to identify the Chinese family business network model. The research method is conducted using a qualitative approach. Based on interviews with several respondents and observations, we found that the business network model has a different pattern on each stage of development and conditions. The network models are increasingly expanding along with business growth. This research has implications for small entrepreneurs to understand the existing model so that it can be used to obtain the resources needed in developing their businesses. Keywords: entrepreneur, social network, family business, chinese ethnic, minority entrepreneur